The Influence of Nurse Compliance Factors and Support Facilities on the Implementation of Hospitals Management Information Systems at a General Hospital District Region Kediri - Topo Rohadi; Ratna Wardani; Indasah (STRADA : Jurnal Ilmiah Kesehatan, 2026)
Hospital Management Information System (SIMRS) is a system used to collect management data from a hospital. The aim of this research is to analyze the influence of nurse compliance factors and supporting facilities on the implementation of the Hospital Management Information System (SIMRS) at the Kediri Regency Regional General Hospital. This research uses a cross sectional study approach with quantitative methods. The population in this study was all 333 nurses at the Kediri Regency Hospital (RSKK).